2018
DOI: 10.1021/acs.iecr.8b02105
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Morphology and Release Behavior of Sorafenib-Loaded Nanocarriers Prepared by Flash Nanoprecipitation

Abstract: Flash nanoprecipitation (FNP) is a recent developed method featuring fast processing and simple equipment for preparing drug-carrier NPs. Herein, we prepared stable sorafenib-loaded NPs with biocompatible amphiphilic poly­(ethylene glycol)-block-poly­(lactide acid) (PEG-b-PLA) as stabilizing polymer based on FNP. The formed NPs show well-controlled size and high drug loading content compared with nanoparticles from traditional antisolvent precipitation. Moreover, drug/polymer mass ratio (D/P) and stream veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
5
6
0
Order By: Relevance
“…As shown in Figure a, as the flow rate increases from 1 mL/min to 7 mL/min, the radius decreases from 142 nm to around 74 nm, reaching the smallest size, and the size distribution is narrower from 0.31 to 0.24 (Figure a). When the flow rates are higher than 7 mL/min (Re ≈ 406), the size remains constant at around 76 nm, suggesting intensive mixing under these conditions. ,,, These results are consistent with the literature results observed for amphiphilic polymer NPs prepared by the RFNP method, where the NP size becomes independent at a high flow rate at a fixed polymer concentration …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…As shown in Figure a, as the flow rate increases from 1 mL/min to 7 mL/min, the radius decreases from 142 nm to around 74 nm, reaching the smallest size, and the size distribution is narrower from 0.31 to 0.24 (Figure a). When the flow rates are higher than 7 mL/min (Re ≈ 406), the size remains constant at around 76 nm, suggesting intensive mixing under these conditions. ,,, These results are consistent with the literature results observed for amphiphilic polymer NPs prepared by the RFNP method, where the NP size becomes independent at a high flow rate at a fixed polymer concentration …”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 2d, there is a drop in light intensity on the ninth day due to the possible sedimentation of the aggregated large-size NC, indicating the instability of the NCs prepared by the conventional method. 17,26 Our results suggest that the RFNP method is more conducive to prepare small and stable NCs than the conventional method; meanwhile, it is demonstrated that nanoscale complexation occurs in different environments in these two processes.…”
Section: 2supporting
confidence: 89%
See 2 more Smart Citations
“…Product properties can obviously be tuned by means of experimental parameters such as solvent/antisolvent ratio, flow rates, and concentrations of solute and stabilizer. FNP has been applied widely to prepare drug-loaded polymeric nanoparticles , because of its typical advantages: simple equipment and proper control of loading capacity and particle size by means of a simple straightforward parameter setting. By means of reactive FNP, metal nanoparticles such as Ag and Pt can be prepared (by reduction of a suitable precursor) and encapsulated in polymeric particles. In these cases, the challenge is again to properly select the reducing and capping agents and to optimize the parameters; in literature reports so far, control over the size and size distribution of metal nanoparticles is still poor.…”
Section: Introductionmentioning
confidence: 99%